Possibilities of ultrasonography in the diagnosis of pigmented villonodular synovitis. Clinical case - V.M. Zhdan; I.V. Ivanytskyi; M.Y. Babanina; T.A. Ivanytska; Y.M. Kitura; H.V. Volchenko; M.V. Tkachenko; O.A. Kyrian; V.H. Lebid (Medičnì Perspektivi)
Pigmented villonodular synovitis is a rare proliferative disease of the synovial membrane, which most often affects the knee joints. Being a benign disease, at the same time, this pathology is often aggressive, and in some cases spreads to the soft tissues outside the joint. There are two forms of monoarticular damage: localized and diffuse. The diffuse form gives frequent relapses. To date, there are no standards for the management of this disease, just as there are no early markers for the detection of pigmented villonodular synovitis. This joint lesion has a long asymptomatic course, or it has symptoms of non-specific recurrent arthritis, so the patients can later be referred for magnetic resonance imaging, which is the only non-invasive method of diagnosing this pathology. At the same time, in modern conditions, most patients with recurrent synovitis will undergo an ultrasound examination of the joint according to the diagnostic standards. Ultrasonography made for abovementioned synovitis is insufficiently described in the medical literature. The aim of our study was to highlight the current data on the diagnosis and management of patients with pigmented villonodular synovitis and to describe our own clinical case. A feature of our clinical case was the detection of characteristic symptoms using ultrasonography. Irregular thickening of the synovial membrane with nodular formations and villous growths, with the length of villi up to 7 mm near the patella with single loci of blood flow, was revealed by ultrasound examination and power Doppler mapping. Shear wave elastometry of the synovial membrane was performed. It demonstrated a significant increase in the stiffness of the synovial membrane, which can be a pathognomonic symptom of this pathology. The diagnosis of villonodular synovitis was confirmed histologically after surgical treatment. Subsequently, the patient had a recurrence of the pigmented villonodular synovitis, which was also detected by ultrasound diagnostics. Thus, pigmented villonodular synovitis of the knee joint is a rather rare pathology that requires differential diagnosis with inflammatory joint diseases. The final diagnosis is based on histological examination. MRI and ultrasound diagnostics are non-invasive methods that can detect this pathology with high accuracy. The advantage of ultrasonography is its availability and non-invasiveness. The increase in stiffness of the synovial membrane along with its proliferation, which we found, can serve as an additional criterion of villonodular synovitis, and, according to the data available to us, has not been described in the literature so far.